Life Cycle Assessment of high ligno-cellulosic biomass pyrolysis coupled with anaerobic digestion. (July 2016) - Righi, Serena; Bandini, Vittoria; Marazza, Diego; Baioli, Filippo; Torri, Cristian; Contin, Andrea
Highlights: Environmental impacts of corn stovers pyrolysis and anaerobic digestion are valued. Biochar is considered as solid fuel for coal power plants or as soil conditioner. All results are compared against a corresponding fossil-fuel based scenario. Results are encouraging although trade-offs are highlighted. Abstract: A Life Cycle Assessment is conducted on pyrolysis coupled to anaerobic digestion to treat corn stovers and to obtain bioenergy and biochar. The analysis takes into account the feedstock treatment process, the fate of products and the indirect effects due to crop residue removal. The biochar is considered to be used as solid fuel for coal power plants or as soil conditioner. All results are compared with a corresponding fossil-fuel-based scenario. It is shown that the proposed system always enables relevant primary energy savings of non-renewable sources and a strong reduction of greenhouse gases emissions without worsening the abiotic resources depletion. Conversely, the study points out that the use of corn stovers for mulch is critical when considering acidification and eutrophication impacts. Therefore, removal of corn stovers from the fields must be planned carefully.